Spontaneous Hybridization between Pinus mugo and Pinus sylvestris at the Lithuanian Seaside: A Morphological Survey - Darius Danusevičius; Vitas Marozas; Gediminas Brazaitis; Raimundas Petrokas; Knud Ib Christensen (The Scientific World Journal)
We address the problem of spontaneous hybridization between an exotic species Pinus mugo and the native/local P. sylvestris at the seaside spit of Kursiu Nerija in Lithuania. The objective was to identify spontaneous hybrids between P. mugo and P. sylvestris based on morphology traits among the individuals naturally regenerating at the seaside spit. The field inventory was carried out over the entire Lithuanian part of the spit, and 200 individuals morphologically intermediate between P. sylvestris and P. mugo were identified. Based on a weighted trait index, the intermediate individuals were grouped into two groups, one morphologically close to P. sylvestris and another close to P. mugo. The needle micromorphological traits of the putative hybrids were of intermediate values between P. mugo and P. sylvestris. The results provide a strong evidence of spontaneous hybridization between P. mugo and P. sylvestris in Lithuanian seaside spit of Kursiu Nerija.